The Metaphors of the Sea in Mar Caníbal by Uriel Quesada - Martínez Alpízar, Diana (2019)
Based on theorization of metaphor made by Paul Ricoeur, this article offers an interpretation of Mar Caníbal (2016), novel written by the Costarrican Uriel Quesada. In this text, the sea is more than a geographic point, it acquires several meanings, according to the developed of the characters. In conclusion, in the text analyzed, the sea, as a polysemantic element, shapes as a metaphor of the danger and the guiltiness, but also it works like a metaphor of the desire and the otherness.